Hubungan Tingkat Pendapatan Keluarga Dengan Prestasi Belajar Siswa SMK Teladan Medan - Simatupang, Dorlince (Universitas Negeri Medan, 2014)
This research aim at: (1) obtaining data on level of family income gradeII students of SMK of FieldByword, (2) findingout achievement of the student grade II SMK offield Byword and,(3)findingÂ out whetherlevel of family income related with studentâs achievement of grade II SMK of Field by word. The research population is student of grade II SMK of Field Byword amount to 50 people, and employing total sampling. Data collecting is used by a Questionnare. Data are analyzed with correlation test (r) and test the level significant 95%. The data analyzedwith correlation test and continued with the test of significant correlation (t) indicate that the correlation coefficient between level of family income with the achievement (rxy) is equal to 0,809 and result of test t calculated: 9,47 and t tables of: 1,68. From the test result that t calculated is bigger than tables of N with the level of significant 95%. T calculated from t off hence hypothesis (ho) refused and alternative hypothesis (ha) accepted. This means that level of family income have positive relation with the student achievement. The result of this research indicate that family income with the mean score 2,76 and correlation coefficient indicate that the level of family incomegive significant contribution to studentâs achievement. Thereby result of this research indicate that the level family income represent one of determinant aspect in improving studentâs achievement.